1998
DOI: 10.1016/s0378-1097(98)00274-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of dnaK and groESL operons during sporulation of Bacillus megaterium

Abstract: Expression of the dnaK and groEL genes during sporulation was assayed by determination of their mRNA levels by Northern blotting and compared with the relative level and rate of synthesis of the corresponding proteins. The ability of sporulating cells to respond to a heat shock by an increase in dnaK and groEL expression was determined at the same time. Synthesis of DnaK and GroEL encoding mRNAs during sporulation in non‐shocked cells was low suggesting that this kind of cytodifferentiation was not accompanied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The findings in this work allow three major conclusions. First, as reported by two other groups (13,21,28), a heat shock at an early time in sporulation results in an increase in wet heat resistance of the resultant spores. This effect does not appear to involve the heat shock response, as there was no elevation in the level of heat shock proteins in the spores with elevated wet heat resistance, as also found in a recent study (21), and we also found that mutations in several heat shock genes did not abolish this phenomenon.…”
mentioning
confidence: 71%
“…The findings in this work allow three major conclusions. First, as reported by two other groups (13,21,28), a heat shock at an early time in sporulation results in an increase in wet heat resistance of the resultant spores. This effect does not appear to involve the heat shock response, as there was no elevation in the level of heat shock proteins in the spores with elevated wet heat resistance, as also found in a recent study (21), and we also found that mutations in several heat shock genes did not abolish this phenomenon.…”
mentioning
confidence: 71%
“…Furthermore, our proteomics pathway analysis revealed that protein chaperones, such as GroEL/S system, and proteins encoded by the heat shock dnaK gene cluster, were increased in relative abundance during the interaction. Previous studies have shown that sporulation in Bacillus megaterium does not increase the levels of GroEL and dnaK chaperones ( Hlaváček et al., 1998 ), which indicates a stress response in P. amylolyticus potentially related to pH drift.…”
Section: Resultsmentioning
confidence: 90%